The Role of Primary School Composition in the Trajectories of Internalising and Externalising Problems across Childhood and Adolescence - Papachristou, Efstathios (J Abnorm Child Psychol, 2019)
There is little research on the role of school and its composition in explaining individual children’s psychological outcomes. This study examined for the first time the role of several primary-school compositional characteristics, and their interactions with individual level characteristics, in the development of two such outcomes, internalising and externalising problems, at ages 7, 11 and 14 years in 4794 children in England participating in the Millennium Cohort Study. Using hierarchical (multilevel) linear models, we found that, even after adjusting for individual and family characteristics, children in schools with higher proportions of pupils eligible for free school meals had more externalising problems. In general, children with special educational needs, lower academic performance, more distressed mothers, and those in non-intact families had more internalising and externalising problems. Our results underline the importance of targeting schools with less affluent overall intakes, but also highlight the key role of individual and family characteristics in the development of their pupils’ psychological functioning.